Internalisasi Konsep Ahlussunnah Wal Jam’ah An-Nahdliyah dalam Penelitian Dosen - Kasanah, Siti uswatun; Ansori, M.Subhan; Nur Safaat, Ahmad Wafi; Ashari, M. Farkhan; Amukti, Candra Febriyan (Universitas Nahdlatul Ulama Blitar, 2024)
The aim of this research is to identify and analyze the concepts and structure of the Aswaja An-Nahdliyah internalization model that are relevant to lecturer research. This research uses the Literature Study method, from various Nahdlatul Ulama text and document sources and FGDs for lecturers to deepen understanding and skills in integrating this concept in research. The results of the internalization of the concept of Ahlussunnah Wal Jama'ah An-Nahdliyah are realized in various research topics that discuss moderate values, inclusive approaches, and adaptive methods in responding to social and cultural problems, not only functioning as a means of scientific development, but also as a medium dissemination of balanced and harmonious Islamic values, which can be a guide for the academic community in carrying out a better academic and social life